Planificación de una unidad didáctica: el estudio del movimiento - García García, José Joaquín; Pro Bueno, Antonio de; Saura Llamas, Octavio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this study we attempt to apply an outline of Teaching Units for the study of Cinematics at Secondary Level. Having analysed the teaching problems indicated by teachers, the scientific contents involved and the methodological problems, a sequence of learning contents is established from a creative construction perspective.